Does ischemic preconditioning preoperatively reduce postoperative pain and analgesic requirement in total knee arthroplasty? - Dubey, Rajiv Ranjan; Behera, Bhabani Shankar; Prasad, Manish (International Journal of Research in Orthopaedics, 2019)
Background: Osteoarthritis of knee is one of the most commonly affecting condition affecting the activities of daily living in the middle age group Indian and Asian population. Total knee arthroplasty (TKA) performed for pain relief and improvement in mobility of individuals is associated with significant post-operative pain. Ischemic preconditioning is one of the non-pharmacologic methods of reduction in postoperative pain using variable periods of tourniquet induced ischaemia which has limited data in literature. Methods: Sample size (n=30) was taken. A standard automatic pneumatic tourniquet was used while performing ischemic preconditioning of the limb prior to TKA and during surgery. Statistical analysis was performed with p values <0.05 considered significant. Standard postoperative analgesia as per hospital protocol was given to patients. Results: The mean 6 hour postoperative and 48-hr postoperative visual analogue scale (VAS) score at rest is significantly higher compared to mean preoperative VAS score at rest (p<0.01 for both). The distribution of mean preoperative and 24 hour postoperative VAS score at rest did not differ significantly (p>0.05). The mean % change in postoperative period compared to preoperative VAS at rest was 47.06%. Conclusions: In this study, the effect of preconditioning over postoperative pain relief was not consistent. Although the patient reported pain scores were low at 6th and 24th postoperative hour, the effect at 48th postoperative hour was not satisfactory. Studies with larger sample size required for better understanding of ischemic preconditioning.